2018
DOI: 10.4082/kjfm.2018.39.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Low Estimated Glomerular Filtration Rate Is Prevalent among North Korean Refugees in South Korea

Abstract: BackgroundThe number of North Korean refugees entering South Korea is rising. Few studies have investigated the risk of non-communicable disease in North Korean refugees. Moreover, kidney insufficiency, a risk factor for cardiovascular disease, has not been studied in this population. We compared the prevalence of non-communicable disease and kidney function in North Korean refugees and South Koreans.MethodsOur study was conducted using a case-control design. We enrolled 118 North Korean refugees from the Hana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Our results are similar with another study wherein the excess weight gain after defection was associated with metabolic syndrome with similar prevalence rate of metabolic syndrome between NKR and SKN (men, 19.7% vs. 26.2%, p = 0.134; and women, 17.2% vs. 16.6%, p = 0.757, respectively) [11]. Another study showed no group difference in the prevalence of NCDs, such as hypertension, diabetes mellitus, and hyperlipidemia; however, general obesity of NKR was higher (NKR vs. SKN, 36.8% vs. 26.7%, p = 0.031, respectively) and abdominal obesity of NKR was lower than that of South Korean counterparts (NKR vs. SKN, 7.7% vs. 18.4%, p = 0.005, respectively) [14].…”
Section: Ncd-related Studiesmentioning
confidence: 78%
See 4 more Smart Citations
“…Our results are similar with another study wherein the excess weight gain after defection was associated with metabolic syndrome with similar prevalence rate of metabolic syndrome between NKR and SKN (men, 19.7% vs. 26.2%, p = 0.134; and women, 17.2% vs. 16.6%, p = 0.757, respectively) [11]. Another study showed no group difference in the prevalence of NCDs, such as hypertension, diabetes mellitus, and hyperlipidemia; however, general obesity of NKR was higher (NKR vs. SKN, 36.8% vs. 26.7%, p = 0.031, respectively) and abdominal obesity of NKR was lower than that of South Korean counterparts (NKR vs. SKN, 7.7% vs. 18.4%, p = 0.005, respectively) [14].…”
Section: Ncd-related Studiesmentioning
confidence: 78%
“…The summary of the characteristics of selected studies is presented in Table 1. It includes 18 quantitative studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and 4 qualitative studies [28][29][30][31]; among the quantitative studies, 5 studies report comparisons with South Korean people [11,[13][14][15]22]. The number of participants in these studies varied from 8 to 932 participants, and 54.6%-100% of them were women.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations